2011
DOI: 10.1155/2011/805275
|View full text |Cite
|
Sign up to set email alerts
|

Associations of −308G/APolymorphism ofTumor Necrosis Factor(TNF)αGene and Serum TNF-αLevels with Measures of Obesity, Intra-Abdominal and Subcutaneous Abdominal Fat, Subclinical Inflammation and Insulin Resistance in Asian Indians in North India

Abstract: Objectives:Obesity is associated with high levels proinflammatory cytokines like tumour necrosis factor alpha (TNF-α), which may play an important role in the genesis of insulin resistance. We evaluated the relationship of −308G/Apolymorphism ofTNF-αgene with obesity and insulin resistance in Asian Indians in north India.Methods:This cross-sectional study included 151 apparently healthy individuals (79 males, 72 females) 18–50 yrs of age from New Delhi, India. Body composition by dual-energy x-ray absorptiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Some studies have demonstrated that the TNF‐α G allele is associated with low TNF‐α production in vitro and in vivo [Kroeger et al, , ; Wilson et al, ; Karimi et al, ; Baghel et al, ]. However, most studies failed to confirm this correlation [Brinkman et al, ps11996; Skoog et al, ; Bayley et al, ; Kaijzel et al, ; Knight et al, ; Cuchacovich et al, ; Marotte et al, ; O'Dwyer et al, ; Vikram et al, ]. Additionally, Mekinian et al [], through a functional study with a meta‐analysis including 21 studies, found no significant association between TNF‐α production and the TNF‐α ‐308 SNP (rs1800629) [Mekinian et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that the TNF‐α G allele is associated with low TNF‐α production in vitro and in vivo [Kroeger et al, , ; Wilson et al, ; Karimi et al, ; Baghel et al, ]. However, most studies failed to confirm this correlation [Brinkman et al, ps11996; Skoog et al, ; Bayley et al, ; Kaijzel et al, ; Knight et al, ; Cuchacovich et al, ; Marotte et al, ; O'Dwyer et al, ; Vikram et al, ]. Additionally, Mekinian et al [], through a functional study with a meta‐analysis including 21 studies, found no significant association between TNF‐α production and the TNF‐α ‐308 SNP (rs1800629) [Mekinian et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an Iranian study did not report any significant association between TNF-α polymorphisms and HBV pathogenesis (Somi et al, 2006). On the contrary, there was not significant relationship between TNF-α polymorphisms and rheumatoid arthritis (Chen et al, 2007;Cuenca et al, 2003;Vikram et al, 2011) and chronic periodontitis Heidari et al, 2014a;Solhjoo et al, 2014) as inflammatory diseases. Although, it seems that TNF-α polymorphisms can block the HBV gene expression via alteration the expression of TNF-α but conflicting data will need further evaluation to show the real effect of TNF-α polymorphisms in HBV infection.…”
Section: Tnf-αmentioning
confidence: 97%
“…The remained articles were further evaluated for appropriateness and 32 articles were excluded (Figure 1). Finally, 15 articles met the inclusion criteria (Fernandez-Real et al, 1997;Walston et al, 1999;Hayakawa et al, 2000;Hoffstedt et al, 2000;Ishii et al, 2000;Rasmussen et al, 2000;Brand et al, 2001;Romeo et al, 2001;Dalziel et al, 2002;Um et al, 2003;Wybranska et al, 2003;De Luis et al, 2011;Vikram et al, 2011;Hedayati et al, 2012;Wingeyer et al, 2012). One article (Ishii et al, 2000) provided separate data on young (aged 21 to 29) and older (aged 45 to 65) subjects, and one article (Hoffstedt et al, 2000) on male and female subjects.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five studies involved lean subjects with normal weight (BMI < 25 kg/m 2 ), 3 involved obese subjects (BMI ≥ 30 kg/m 2 ), and 9 involved both obese and lean subjects. The genotype distributions in two studies were deviated from HWE (Wybranska et al, 2003;Vikram et al, 2011). The studies were published between 1997 and 2012.…”
Section: Study Characteristicsmentioning
confidence: 99%